Cyclooxygenase-2 as potential intervention target of leprosy reactions: a systematic review - Rusyati, Luh Made Mas; Sari, Luh Gede Melia Puspita; Winaya, Ketut Kwartantaya (Bali Dermatology Venereology and Aesthetic Journal, 2023)
Background: Leprosy reaction is an acute inflammatory of leprosy complication that potentially cause disability. Prompt and appropriate treatment is needed to prevent this permanent neurological complication. As inflammation of this reaction is mediated by cyclooxygenase-2 (COX-2), therefore targeting this substance may potential to prevent disability. This systematic review aimed to define COX-2 as a potential target of intervention in leprosy reaction. Method: Medline, Cochrane library, PubMed, and Google scholar databases were searched for articles published at any time. Observational study and clinical trial, comparative, prospective, retrospective, and descriptive study were extracted, analyzed, and discussed. Results: We found 6 studies that met the inclusion and exclusion criteria, with 104 participants with leprosy reactions and 143 comparators included in this review. In leprosy reactions, COX-2 expression was found in the vessels and nerves of the dermis and subcutis. Macrophages are cell mostly abundantly expressing COX-2. The COX-2 expression was found higher in the leprosy reaction compare to the non-leprosy reaction. Genetically, genes PTGS2 and TNFAIP6 encode COX-2 production also tend to increase especially in type 1 reaction. Conclusions: Preclinically and genetically, COX-2 is a potential target for intervention of leprosy reaction.